2013
DOI: 10.1111/ijfs.12125
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and antioxidant activity of a synthetic cocoa butter equivalent obtained through modification of mango seed oil

Abstract: This research describes the interesterification of Malaysian mango seed oil (MSO) and palm oil mid-faction (POMF) to develop a cocoa butter equivalent. Fat blends, formulated by binary blends of palm oil mid-fraction and mango seed oil at different ratios ({100:0}, {60:40}, {50:50}, {40:60}, {0:100}), were subjected to enzymatic interesterification. The solid fat content revealed that all interesterified blends except 100% POMF {0:100} melted completely at body temperature. The interesterified {50:50} blend ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
3
8
1
Order By: Relevance
“…The iodine value determined for BKF is shown in Table 3. The iodine value for BKF in this study was higher compared to the reported iodine values for some mango seed fats by Momeny et al (2013), Jahurul et al (2014b) and for commercial CB by Chaiseri & Dimick (1989). Conversely, it was lower when compared to the reported iodine values for zebda, balady and succary mango fats by Abdalla et al (2007).…”
Section: Iodine Valuecontrasting
confidence: 86%
See 2 more Smart Citations
“…The iodine value determined for BKF is shown in Table 3. The iodine value for BKF in this study was higher compared to the reported iodine values for some mango seed fats by Momeny et al (2013), Jahurul et al (2014b) and for commercial CB by Chaiseri & Dimick (1989). Conversely, it was lower when compared to the reported iodine values for zebda, balady and succary mango fats by Abdalla et al (2007).…”
Section: Iodine Valuecontrasting
confidence: 86%
“…Arachidic, linoleic and linolenic acids were the remaining fatty acids (Table 1). The major fatty acids content of BKF was in close agreement with that of mango seed fats reported by Abdalla et al (2007), Momeny et al (2013) and Jahurul et al (2014b). However, the contents varied to a small extent from those reported by Muchiri et al (2012) for different mango varieties.…”
Section: Fatty Acidssupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the fat phase, in conformity to various studies, palmitic, stearic and oleic acid were the three major fatty acids in all sampled mango fats [9,12,45,47]. Due to seasonal and varietal variation, the relative fatty acid composition may alter.…”
Section: Discussionsupporting
confidence: 71%
“…The StOSt content gives an indication of the heat resistance, hence, fats enriched in this fraction act as cocoa butter improver and decrease the tempering time of chocolate [7,9]. For more than three decades, mango kernels from different varieties/origins has inspired a lot of researchers to study its fat phase (MF) showing both physically and chemically similitude to that of cocoa butter [9][10][11][12][13][14][15][16]. Only one study was conducted on MF composition from Vietnamese origin [17].…”
Section: Introductionmentioning
confidence: 99%